The complete book of drawing optical illusions and spiral art - Harris, Jonathan Stephen; Pabst, Stefan, 1980- (Walter Foster, 2023)
The Complete Book of Drawing Optical Illusions, 3D Illustrations, and Spiral Art is a comprehensive reference guide to help you master more than 50 optical illusions, 3D illustrations, and spiral drawings.